PENERAPAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KELAS IV SD NEGERI 002 KEPENUHAN HULU - Seriwati Seriwati (STKIP ROKANIA, 2020)
Audio visual media can be used as a medium that allows students to learn efficiently especially on thematic learning in elementary school. Based on the observation results in class IV SD Negeri 002 kepenuhan hulu, teachers have not been able to use the learning media Right in the classroom teaching and learning activities, the teacher simply describes the material, while the students are less active in learning and only listen to the explanation from the teacher, so that the student learning outcomes are still gaining value in Under the KKM. The problem formulation in this research is how the application of visual audio media to improve student learning outcomes of grade IV SD Negeri 002 downstream. The purpose of this research is to find out how the application of audio visual media in the thematic learning of grade IV students elementary School 002 downstream. This research is class action research (PTK) by using 2 cycles each cycle there are 2 times the meeting. The instruments used in this study are learning devices (syllabus and RPP, teacher and student observation sheet) data analysis techniques by analyzing student learning outcomes and student activities, based on research gained learning outcomes Students on Cycle 1 students who are complete with a percentage of 57.14% with a good enough category on the II cycle which students with a percentage of 90.48% with the category at all, from the research done can be concluded that the application of audio visual media to Improve the learning outcomes of grade IV Students Elementary School 002 Kepenuhan Hulu.